The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1063/1.5050133
|View full text |Cite
|
Sign up to set email alerts
|

The potency of gadung (Dioscorea hispida Dennst.) tuber as a functional food: Toxicity, phytochemical content and starch characters

Abstract: The research aimed to know the toxicity, phytochemical contents and starch characters of gadung tuber collected from Timor Leste, Kalimantan Tengah, and Special Region of Yogyakarta. Dry tubers were prepared for toxicity, and phytochemical contents analyses and fresh tuber were used to observe the character of gadung starch. Tubers were extracted by soxhlet apparatus using chloroform and methanol. The toxicity of gadung tuber was done using Brine Shrimp Lethality Test (BSLT). Effect of toxicity from each extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
0
0
2
Order By: Relevance
“…Moreover, the water content of D. hispida sample was in the range of 7.96% to 37.8%, the lowest among the yam species such as D. bulbifera (69.5%) and D. versicolor (80.2%) (Harijono et al, 2013;Saleha et al, 2018). However, the nutritional compositions may differ when affected by factors such as soil conditions, pH, organic matter, climate, and postharvest handling and storage (Behera et al, 2010;Nugroho & Estyaniyana, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the water content of D. hispida sample was in the range of 7.96% to 37.8%, the lowest among the yam species such as D. bulbifera (69.5%) and D. versicolor (80.2%) (Harijono et al, 2013;Saleha et al, 2018). However, the nutritional compositions may differ when affected by factors such as soil conditions, pH, organic matter, climate, and postharvest handling and storage (Behera et al, 2010;Nugroho & Estyaniyana, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Kamaruddin et al (2020) suggested that the usage of sodium chloride solution helped in removing the toxin alkaloid in D. hispida tuber in a shorter period to avoid food poisoning. However, dioscorine tuber contents may be varied as it can be affected by various factors including environmental conditions and genetic factors (Nugroho & Estyaniyana, 2018). Plants containing alkaloids were widely used in both traditional and modern medical practices.…”
Section: Resultsmentioning
confidence: 99%
“…BSLT is one of the effective in vitro assays to evaluate the cytotoxicity substance using a biological model, Artemia salina. The assay was conducted according to Laurentius et al (2018) with slight modifications. Briefly, the cysts were initially hatched in the artificial seawater for 48 hours.…”
Section: Toxicity Test In Vitro -Bsltmentioning
confidence: 99%
“…Di beberapa daerah di Indonesia termasuk di Provinsi Jawa Barat, umbi gadung sering diolah menjadi berbagai makanan. 1 Namun umbi gadung mempunyai kandungan alkaloid beracun bernama senyawa diocscorin dan kadar HCN tinggi yang dapat mengakibatkan mual, muntah dan pusing jika dikonsumsi secara langsung atau jika penanganannya tidak tepat. Hal ini menyebabkan umbi gadung kurang diminati.…”
Section: Pendahuluanunclassified
“…Ekstrak cair yang diperoleh kemudian disaring dan filtratnya dipekatkan sehingga diperoleh ekstrak kental. Persentase rendemen dihitung dengan rumus yang terdapat pada persamaan (1).…”
Section: Tahap Ekstraksi Umbi Gadungunclassified